2000
DOI: 10.1007/bf03343737
|View full text |Cite
|
Sign up to set email alerts
|

Leptin levels in relation to body composition and insulin concentration in patients with endogenous Cushing’s syndrome compared to controls matched for body mass index

Abstract: Cushing's syndrome (CS) is associated with weight gain and visceral obesity. We examined the relationship between regional fat distribution and serum levels of leptin, cortisol and insulin. Twenty-three consecutive patients with recently diagnosed CS (18 with pituitary adenoma, 5 with adrenal tumor), where compared to obese controls, matched for age, sex and Body Mass Index (BMI). Serum insulin, leptin, cortisol, C-peptide and body composition determined by DEXA were measured. Serum leptin levels were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 39 publications
0
18
1
1
Order By: Relevance
“…First, circulating leptin level is correlated with the body fat mass in dogs,21 so it is possible that an increased fat mass in the abdomen might lead to excessive hyperleptinemia. Second, in humans, it has been suggested that an increase in visceral fat has a relatively stronger effect on serum leptin in patients with Cushing's syndrome than it does in subjects with normal cortisolemia 22, 23, 24, 25. Therefore, it is also possible that an excess of endogenous cortisol promotes the production of leptin by adipose tissue without a change in fat mass 24.…”
Section: Discussionmentioning
confidence: 99%
“…First, circulating leptin level is correlated with the body fat mass in dogs,21 so it is possible that an increased fat mass in the abdomen might lead to excessive hyperleptinemia. Second, in humans, it has been suggested that an increase in visceral fat has a relatively stronger effect on serum leptin in patients with Cushing's syndrome than it does in subjects with normal cortisolemia 22, 23, 24, 25. Therefore, it is also possible that an excess of endogenous cortisol promotes the production of leptin by adipose tissue without a change in fat mass 24.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of adults with CS report a phenotype of higher abdominal and truncal fat percentages (as measured by dual-energy X-ray absorptiometry), intra-abdominal fat deposit (as measured by computed tomography) and reduced lean mass percentage compared with body mass index (BMI)- and age-comparable controls 1, 2 . In addition, studies with adult patients report that CS is associated with increased intra-abdominal fat stores compared to subcutaneous fat 35 .…”
Section: Introductionmentioning
confidence: 99%
“…A variety of hormones have been shown to regulate leptin production both in vitro and in vivo, including insulin and cortisol (7-10). Thus, the fat distribution associated with CS (11-14) has been linked to elevated plasma leptin levels (11,15,16), although the pathophysiological significance of leptin overproduction in these patients is, at present, unclear. Different mechanisms have been proposed for this apparent leptin resistance, including reduced efficiency of brain leptin transport and increased levels of soluble leptin receptor acting as a decoy for ligand signaling (17).…”
mentioning
confidence: 97%